1997
DOI: 10.1161/01.hyp.30.5.1135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Correlates of Microalbuminuria in Essential Hypertension

Abstract: The prevalence of microalbuminuria and its relationship with several cardiovascular risk factors and target organ damage were evaluated in a cohort of 787 untreated patients with essential hypertension. Albuminuria was measured as the albumin-to-creatinine ratio in three nonconsecutive, first morning urine samples. The prevalence of microalbuminuria was 6.7%. Albuminuric patients were more likely to be men and to be characterized by higher blood pressure, body mass index, and uric acid levels and lower HDL cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
88
4
10

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(114 citation statements)
references
References 30 publications
12
88
4
10
Order By: Relevance
“…Thus, it appears that patients with higher LVMI and IMT (ie those in cluster no 1) also have higher UAE values. Moreover, the clustering of UAE with higher values of LVMI and IMT is in agreement with previous reports by our group and by others, 10,[21][22][23] and indicate an association among microalbuminuria, LVH and carotid atherosclerosis. Therefore, measuring urinary ACR, a simple, low cost and readily available test, can be regarded as a cost-effective way to identify, among the large number of hypertensive patients, those who need additional preventive measures and/or more aggressive antihypertensive treatment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, it appears that patients with higher LVMI and IMT (ie those in cluster no 1) also have higher UAE values. Moreover, the clustering of UAE with higher values of LVMI and IMT is in agreement with previous reports by our group and by others, 10,[21][22][23] and indicate an association among microalbuminuria, LVH and carotid atherosclerosis. Therefore, measuring urinary ACR, a simple, low cost and readily available test, can be regarded as a cost-effective way to identify, among the large number of hypertensive patients, those who need additional preventive measures and/or more aggressive antihypertensive treatment.…”
Section: Discussionsupporting
confidence: 93%
“…These criteria proved to have good sensitivity and specificity in detecting albumin excretion rates between 20 and 200 g/min. 10,11 Electrocardiography Standard ECGs were evaluated to detect LVH. LVH was defined by the presence of at least one of two electrocardiographic criteria: the Sokolow-Lyon voltage and the gender-specific Cornell voltage.…”
Section: Albuminuriamentioning
confidence: 99%
“…Details of the study have already been published. 12 Exclusion criteria included the presence of neoplastic, hepatic and/or renal disease (serum creatinine 41.4 mg/dl for females and 41.5 mg/dl for males and/or proteinuria 4300 mg/ 24 h), chronic heart failure (NYHA classes III and IV), a positive history or clinical signs of ischaemic heart disease, diabetes mellitus, severe obesity (defined as body weight 4150% of the ideal body weight), and/or disabling diseases such as dementia or inability to co-operate. The diagnosis of essential hypertension was made by the attending physician after a complete medical history, physical examination, and routine biochemical analyses of blood and urine were obtained from each patient.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…Low-density lipoprotein (LDL)-cholesterol was calculated using Friedewald's formula. The presence of microalbuminuria was evaluated in each patient by measuring the albumin to creatinine ratio (ACR) on three non consecutive first morning samples as described in Pontremoli et al 12 In order to account for differences in basal creatinine excretion rates and body mass index (BMI), different values were used to define microalbuminuria in males (ACRX2.5 mg/mmol) and in female subject (ACRX3.5 mg/mmol). Family history and lifestyle habits were assessed by means of a standard questionnaire.…”
Section: Selection Of Patientsmentioning
confidence: 99%
“…1,2,4-6 The pathogenic mechanisms leading microalbuminuric patients to this increased risk are still unknown; several studies have demonstrated an association between microalbuminuria and atherogenic cardiovascular risk factors, endothelial dysfunction, impaired aortic mechanics and increased left ventricular (LV) mass. 2,[5][6][7][8] Left ventricular hypertrophy is another manifestation of pre-clinical disease with well-defined prognostic meaning for cardiovascular complications. Furthermore, identification of various geometric patterns of LV hypertrophy furthers stratifies cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%